2001
DOI: 10.1088/0022-3727/34/16/320
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence, recombination induced luminescence and electroluminescence in epoxy resin

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link ABSTRACTDielectric breakdown of epoxies is preceded by light emission, or so-called electroluminescence, from the solid-state material. Very little is known about the luminescence properties of epoxies. The aim of this paper is to derive information that can be used as a basis to understand the nature of the excited states and their involvement in electrical degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
4
15
0
1
Order By: Relevance
“…In addition, recent charging studies at Utah State University (USU) using low-flux intermediate-energy electron beams on thin film highly disordered SiO 2 samples exhibited not only cathodoluminescent behavior 3,11-14 but also occasional arcing under some conditions. Similar behavior was also observed in experiments for other dielectric materials including cyanate ester and epoxy resins in graphite and fiberglass composites 2,9 and Kapton HN TM polyimide and carbon-loaded polyimide nanodielectric composites 2,13 . These results suggest that materials used in structural components, optical elements, and thermal control surfaces of spacecraft and space-based observatories could, when exposed to the space plasma environment, luminesce.…”
Section: Introductionsupporting
confidence: 81%
“…In addition, recent charging studies at Utah State University (USU) using low-flux intermediate-energy electron beams on thin film highly disordered SiO 2 samples exhibited not only cathodoluminescent behavior 3,11-14 but also occasional arcing under some conditions. Similar behavior was also observed in experiments for other dielectric materials including cyanate ester and epoxy resins in graphite and fiberglass composites 2,9 and Kapton HN TM polyimide and carbon-loaded polyimide nanodielectric composites 2,13 . These results suggest that materials used in structural components, optical elements, and thermal control surfaces of spacecraft and space-based observatories could, when exposed to the space plasma environment, luminesce.…”
Section: Introductionsupporting
confidence: 81%
“…Charging studies on polymers and carbon composites have revealed that sample arcing and luminescence occur as a result of electron beam bombardment [3][4][5]. Both insulating regions and electrically isolated carbon particles (floating conductors) can accumulate and dissipate charge; cathodoluminescence results from the insulating polyimide regions.…”
Section: Introductionmentioning
confidence: 99%
“…Two forms of electron-induced light emission have been commonly encountered, both of which emit light from large surface areas that have been charged by the incident electron flux [4,5]. Continuous emission observed whenever a material is exposed to electron fluxes is termed "glow," or more properly, cathodoluminescence (CL) [4,[6][7][8]. Intermediate-duration light emissions events, which start with a large rapid spike in intensity similar to arcs and are followed by an exponential decay (~10-100 s decay constant) back to the continuous equilibrium CL intensity, have also been observed for several polymeric and composite materials [1,5].…”
Section: Introductionmentioning
confidence: 99%